Indigenous peoples' responses to land exclusions: emotions, affective links and power relations. Issue 3 (21st March 2022) - Hak, Sochanny; Underhill-Sem, Yvonne; Ngin, Chanrith
Abstract: Drawing on ethnographic research, this paper discusses indigenous peoples' emotional responses to land exclusions in two Bunong villages, Mondulkiri Province, Cambodia. We examine how villagers responded to land exclusions brought about by both state-sponsored conservation and economic land concessions. To understand their responses, we work with the concept of emotions as an embodiment of both personal and collective experiences, to draw attention to the range of feelings, thoughts and expressions that emerge during environmental conflicts. Where local responses to land exclusions appear successful in changing the impact of land exclusions in favour of indigenous peoples, we find that both positive and negative emotions, especially those of local leaders, are important. Further, collective emotional responses to prevent continued land encroachments can shift the power of state actors by subjecting them to the embodied demonstrative strength of community demands. The power dynamics shows how attention to emotions provides a deeper understanding of seemingly contradictory responses by indigenous peoples to land exclusions. We conclude by returning to the importance of local leadership because while collective emotions can be positive catalysts for initiating, empowering and keeping the momentum of a movement, individual leaders need to be comfortable with embodying their own, often contradictory, emotions.